The Design of a Website as a Digital Promotion Media for Kejawanan Beach Cirebon City - Aura Dwi Tasya Aura; Atikah Nurhayat; Mochamad Candra Wirawan Arief; Juliandri Prihadi; Ahmad Prawira Dhahiyat (Jurnal Pariwisata Nusantara (JUWITA), 2025)
Purpose: This study aims to design a website as a digital promotional media for Kejawanan Beach in Cirebon City, which provides accurate and real-time information for tourists. Website design can also be one of the competitiveness in terms of tourism promotion with other tourist destinations, because website design can display visual and narrative appeal so that it can arouse the interest of potential visitors. Method: The research method used is qualitative, with primary data collected through observation and interviews, as well as secondary data from tourism management policies. The website development process began with data collection through observation and interviews with managers and visitors, followed by concept design, sitemap creation, and design development using WordPress. Result: The results of this study are expected to be a reference for Kejawanan Beach managers to improve digital promotion and make it easier for tourists to obtain information related to the destination. The design of the Kejawanan Beach digital promotion website is designed to introduce the natural beauty and various tourist activities on the beach, such as swimming, boating, mud therapy, mangrove conservation and fishing. Visitors can enjoy virtual tours, find accommodation, restaurants, and buy souvenirs typical of marine tourism online. Contribution: This research contributes to the development of digital promotion for Kejawanan Beach through the design of a website that facilitates tourists in accessing information. The results are expected to serve as a guide for managers in enhancing digital-based promotional strategies and as a reference for literature on digital media as a tourism promotion tool.